Seismic performance of semi-rigid steel-concrete composite frames. (April 2020) - Senthilkumar, R.; Satish Kumar, S.R.
Abstract: Steel-concrete composite frames with semi-rigid connections can be designed to resist earthquakes in low to moderate seismic zones by ensuring that they have adequate strength, stiffness and ductility. However, the design of semi-rigid composite frames to ensure desirable seismic performance is a complex problem due to several issues such as calculation of flexural stiffness of the composite beam, evaluation of the storey drifts and defining the secant stiffness of the nonlinear connection. In this paper, issues in the design of semi-rigid composite frames are discussed and proposed preliminary design guidelines for semi-rigid steel-concrete composite frames to satisfy the drift limits and give acceptable performance. Seismic performance of frames designed as per the force based design and direct displacement based design is compared and found that direct displacement based design is not promising in low seismic zones in terms of utilisation of material.